The Pathway Towards Low Carbon Schools: Criteria, Targets and Solutions - Jesús Lizana (Nova, 2022)
This publication summarizes a long period of research on the environmental performance of schools inside the framework of the ClimACT project (2016-2019). It proposes a methodological approach towards a low-carbon economy based on two main actions for environmental education in schools: measuring the environmental performance of school communities through a school sustainability index based on measurable indicators in the areas of transport, procurement, green spaces, indoor air quality, energy, water and waste; and encouraging students, teachers, and families towards an energy-efficient and low-carbon pathway through a structural procedure based on roles, activities and progress evaluation. The book includes the results of 39 pilot schools in Europe before and after implementing the methodology and the catalog of low-carbon activities and solutions proposed and implemented to empower school communities towards a low-carbon economy.